Dinámicas literarias y poéticas centroamericanas del siglo XXI (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2024)
In these research notes a brief historiographic panorama is developed around some of the most recent Central American literary and poetic dynamics that tend to happen also in other Latin American and European countries, including, although some cases had been brewing since the 1980s, particular points of discussion of the first two decades of the 21st century. In list, the following facts: acceleration of cybernetic networks and in a concerted manner, publications in digital literary magazines, virtual meetings, increase of information platforms and publications in international publishing imprints; constant migrations and exiles; greater number of international poetry festivals (virtual or not); literary contests; new dictatorships; political and economic crises; emancipation of Abyalense and Afro-descendant voices; increase in the creation of cartonera publishing houses and avant-garde waves of works written by women. The methodology uses field research (interviews and personal communications) and review of academic references. The information gathered here intends to contribute to future and eventual research dedicated to the literary analysis of poems published during the last years by Central American authors.